ICRITC-24 REVIEW: Proceedings of the International Conference on the Renewal and Reform of Islamic Thought and Civilisation - Ahmad, Khaliq; Norman, Nurul Ain (ISTAC, 2024)
International Conference on the Renewal and Reform of Islamic Thought and Civilisation (ICRITC’24) © 2024 by ISTAC-IIUM Publication (e ISBN 978-983-9379-76-1).